PHILANTHROPY of WAQF WELLS to MITIGATE THE IMPACT of DROUGHT IN MON IKEUN VILLAGE, LHOKNGA, ACEH BESAR - Rahmah, Siti; Yulfan, Yulfan; Marlenny, Hemma; Megawati, Cut; Gunawan, Teguh (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2025)
AbstractDrought is a natural disaster caused by a deficit in rainfall over a certain period of time which causes insufficient water availability for human activities and the environment. Mon Ikeun Village is one of the villages experiencing a shortage of water availability. Therefore, it is necessary to provide adequate water to anticipate drought in Mon Ikeun village. This service aims to carry out humanitarian aid activities for drought in Gampong Mon Ikeun by providing well waqf, apart from being a form of humanity it is also a form of investment in the hereafter. This service uses qualitative analysis methods data collected through field surveys and interviews with the community to obtain the required data. The results of this service show that the provision of well waqf is very effective in increasing access to clean water and reducing dependence on unsecured water sources.Keywords: Drought, Water availability, Well waqf Abstrak Kekeringan merupakan bencana alam yang diakibatkan oleh kerusakan lingkungan dan defisit curah hujan dalam periode waktu tertentu yang menyebabkan tidak cukupnya ketersediaan air untuk kegiatan manusia dan lingkungan. Gampong Mon Ikeun menjadi salah satu desa yang mengalami kekurangan ketersediaan air. Maka dari itu dibutuhkan penyediaan air yang memadai untuk mengantisipasi kekeringan di Gampong Mon Ikeun. Pengabdian ini bertujuan  untuk melakukan kegiatan bantuan kemanusiaan kekeringan di Gampong Mon Ikeun dengan menyediakan wakaf sumur, selain sebagai bentuk kemanusiaan juga sebagai bentuk investasi akhirat. Pengabdian ini menggunakan metode analisis kualitatif. Data yang dikumpulkan melalui survei lapangan dan wawancara kepada masyarakat untuk memperoleh data yang dibutuhkan. Hasil dari pengabdian ini menunjukkan bahwa penyediaan wakaf sumur sangat efektif dalam meningkatkan akses air bersih dan mengurangi ketergantungan pada sumber air yang tidak terjamin.Kata Kunci : Kekeringan, Ketersediaan air, Wakaf sumur